A new species of Lygistorrhina (Lygistorrhina) Skuse, 1890 (Diptera: Keroplatidae, Lygistorrhininae) with a key to the subgenus - Blagoderov, Vladimir; Ollerton, Jeff; Whittington, Andrew (Zootaxa, 2023)
A new species of Lygistorrhina (Lygistorrhina) Skuse, 1890, Lygistorrhina woodi sp. nov., is described. The specimen was dissected from an alcohol-preserved flower of Ceropegia aristolochioides ssp. deflersiana Bruyns (Apocynaceae, Asclepiadoideae, Ceropegieae) stored in the Kew herbarium. This is the first occurrence of the lygistorrhine gnats in a hot, semi-arid climate. A key to all known species of the subgenus Lygistorrhina (Lygistorrhina) is provided.